MANAGEMENT OF NEGLECTED VICIOUS CAT BITE IN A CHILD: A CASE REPORT - Tarmalinggam, Shangeetha; Chandrasekaran, Sree Raja Lakshmy; Mohd Asihin, Muhammad Azrin; Abdul Ghani, Kamarul Al-Haqq (Sanamed, 2022)
Introduction: Cat bites make up 10% of all animal bites and have a high incidence of infection. Cat bites can cause severe deep bacterial infection in closed spaces such as tendon sheath, joints, and bones due to their sharp teeth. Generally, cat bite wound infections are reported at 30%-60%, which is double compared to rat or dog bites. However, cat bites are easily misjudged due to their minimal appearance of tissue injury. Case Report:We hereby present a case of a neglected cat bite wound complicated with infection in a healthy child. The wound was debrided in the operation theatre, and a ten-day course of antibiotics was completed. No further infection was noted and the child was discharged home well. Conclusion:There is no exact algorithm of treatment for cat bites. However, cat bites are nasty wounds that should be treated early and aggressively. Empirical oral or intravenous antibiotics should be started immediately, and adequate surgical debridement is indicated to provide a better outcome as there are no standardized protocols for initial management.
Keywords: cat bite; infection; wound; Antibiotic Treatment